2015
DOI: 10.1039/c5sm00865d
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing hydrogels containing reversible oxime crosslinks

Abstract: Self-healing oxime-functional hydrogels have been developed that undergo a reversible gel-to-sol transition via oxime exchange under acidic conditions. Keto-functional copolymers were prepared by conventional radical polymerization of N,N-dimethylacrylamide (DMA) and diacetone acrylamide (DAA). The resulting water soluble copolymers (P(DMA-stat-DAA)) were chemically crosslinked with difunctional alkoxyamines to obtain hydrogels via oxime formation. Gel-to-sol transitions were induced by the addition of excess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(123 citation statements)
references
References 78 publications
0
121
0
1
Order By: Relevance
“…Self‐healing hydrogels offer substantial benefits to extend the life span of hydrogel material due to its excellent intrinsic healing ability to repair themselves after destruction. Nowadays, the preparation of self‐healing hydrogels is mainly based on dynamic chemistry, including dynamic covalent chemistry and non‐covalent chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…Self‐healing hydrogels offer substantial benefits to extend the life span of hydrogel material due to its excellent intrinsic healing ability to repair themselves after destruction. Nowadays, the preparation of self‐healing hydrogels is mainly based on dynamic chemistry, including dynamic covalent chemistry and non‐covalent chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…S2), which further indicated irreversible breakage of covalent bonds within the polymer network. 45, 46 On the other hand, there was no significant difference between the measured G’ and G” values between the virgin D10L2/DN and those that were compressed to a strain of 0.5. This result further confirmed that the presence of DMA and Laponite minimized changes to the mechanical properties and the architecture of the DN hydrogel.…”
Section: Resultsmentioning
confidence: 85%
“…Over the last decades, many DCBs have been reported based on for example, imine exchange, transesterification, olefin metathesis, reversible boronic ester formation, and dichalcogenide bond exchange . In addition, various studies on CLPs, including DCBs, have revealed that CLPs that contain DCBs show a variety of functionalities, such as self‐healing, shape memory, reversible sol‐gel reactions, stress relaxation, and reprocessing . Especially self‐healing based on bond‐exchange reactions is expected to prolong the lifetime of materials by preventing fatal structural disintegration.…”
Section: Figurementioning
confidence: 99%